(untitled) (Communication & Society, 2015)
The current high public deficit situation of the Spanish economy lead us to analyse the management of public service companies, their allocation of resources and how well they are used. Within this article, we shall compare the efficiency of regional public service broadcasters (PSBs) in Spain using Data Envelopment Analysis (DEA) method and benchmarking. That will be done with two goals in mind. One, to evaluate and compare the performance of regional public television networks. And two, to propose policy measures to improve management efficiency. The results from the study indicate that more than a half of public television services in Spain are inefficient. It is recommended that the television services change some of their inputs/outputs to enhance efficiency and ensure future sustainability